Men Trust, Women Verify? The Power of Logo Verification in Driving Purchase Intentions of Halal Cosmetics - Mahnoor Ashraf; Dr. Yasir Tanveer; Dr. Anum Tariq (Indus Journal of Social Sciences, 2025)
This research investigates the impact of awareness of halal, halal logo verification, and gender on consumers' attitudes towards halal cosmetics in Faisalabad, Pakistan. Data were collected from 200 consumers using a quantitative, cross-sectional survey questionnaire of a 5-point Likert scale. The study used hierarchical regression and the moderated moderation technique based on PROCESS Macro to test three key hypotheses. By establishing the research model, it was found that there is a strong positive relationship between the Halal awareness factor and purchase intention, which indicates that the Halal consciousness factor affects the consumption of Halal cosmetics. It was also found that halal logo verification had a moderating effect, which suggests that the perceived awareness leads to higher intention when there is a visible certification. Interestingly, there were varying analyses of verification reliance across gender. Although both genders expressed their concern for halal certification, female consumers were found to be more reliant on logo verification than male consumers. For women, indeed, only the highest level of verification produced a marked increase in the purchase intention, whereas for men, the response was relatively flat across all levels of verification. This study adds to the current literature on halal marketing by identifying how verification requirements, distinct for males and females, affect purchasing behaviour in one of the emerging markets for halal cosmetics. This study offers real-world implications for businesses, stating that visibility of being authentically halal certified, especially when dealing with female customers, can make a big difference in consumer desire to purchase the products. The study discusses the synergetic relationship of religious conformity and consumers' behavior in the context of Pakistan's 'halal' economy and the managerial and theoretical implications for moving the halal economy forward.